WHAT TO DO WITH A VARIETY OF TERMS THAT REFLECT THE HARM OF DRUGS? - Yu. V. Muravyev; L. A. Muravyeva (Научно-практическая ревматология, 2017)
The discussion provides evidence for the long-felt need to standardize the terms reflecting the harm of drugs.